POLITICAL AND SOCIAL SITUATION OF GERMANS IN SOUTH KAZAKHSTAN DURING THE FIRST WORLD WAR - Apendiyev T.А. (Scientific Journal of Pedagogy and Economics, 2020)
At the beginning of the twentieth century, the South Kazakhstan region, namely Aulieata and Shymkent (Chernyaev) districts, was one of the main German settlements. These areas, which belong to the Syrdarya region of the Turkestan region, have been inhabited by Germans since the last quarter of the 19th century and are considered to be one of the main European ethnic groups. The Germans interacted with the local population and contributed to the development of ethno-demographic processes in the region. However, the development of such processes and the political and social life of the Germans had a negative impact on the First World War. At the beginning of the twentieth century, this war, which was a major international factor, created a great war between the empires, and it also divided the peoples. From the first days of the First World War, 1914-1918, relations between the Russian Empire and Germany were at war. This situation changed the political life of the Germans and the German community living in the Russian Empire. Such changes took place especially in the lives of German settlers in the European part of the empire. His main examples were the military persecution of Germans, the stigmatization of Germans in society, the establishment of chauvinistic attitudes among ethnic groups, and similar factors. In Russia, local Germans have been labeled "internal enemies." The fate of German communities in all regions of the Russian Empire was closely monitored in 1914-1918, and in general, since 1914, the fate of the Germans has been very constructive. At the same time, there is a legitimate question as to whether the situation in the Turkestan region is the same as in other regions of the Russian Empire. Similarly, the article raises questions about the situation of Germans in Shymkent and Aulieata districts of the Syrdarya region, and seeks answers in this regard. The article examines the political situation and social life of Germans in the South Kazakhstan region during the First World War. The main task of the article is to show the life of local Germans and their place in society. In addition, the political and social history of other peoples in the region will be considered.